2017
DOI: 10.3748/wjg.v23.i48.8553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of totally laparoscopic total gastrectomy using an endoscopic linear stapler with laparoscopic-assisted total gastrectomy using a circular stapler in patients with gastric cancer: A single-center experience

Abstract: AIMTo evaluate the safety and efficacy of totally laparoscopic total gastrectomy (TLTG) with esophagojejunostomy using a linear stapler compared with laparoscopic-assisted total gastrectomy (LATG) using a circular stapler in gastric cancer patients.METHODSWe retrospectively reviewed 687 patients who underwent laparoscopic total gastrectomy for gastric cancer at a single institution from August 2008 to August 2014. The patients were divided into two groups according to the type of operation: 421 patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 38 publications
(40 reference statements)
4
38
0
4
Order By: Relevance
“…However, there are some problems associated with these procedures, namely LTG is a very recently introduced procedure compared with laparoscopic distal gastrectomy. In particular, the technique for performing esophagojejunostomy is controversial [4,5]. Gastroesophageal reflux can occur after LPG, prompting various types of reconstruction, a standard procedure not yet having been established.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some problems associated with these procedures, namely LTG is a very recently introduced procedure compared with laparoscopic distal gastrectomy. In particular, the technique for performing esophagojejunostomy is controversial [4,5]. Gastroesophageal reflux can occur after LPG, prompting various types of reconstruction, a standard procedure not yet having been established.…”
Section: Introductionmentioning
confidence: 99%
“…These anastomosis techniques are less technically complex. They can effectively prevent the occurrence of anastomotic stenosis (23)(24)(25)(26). However, the closure of the joint opening with the Endo GIA makes the overlap procedure easier but tends to cause stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 ± 9 . 4 ( 2 6 -4 1 ) m i n , intraoperative bleeding was 141.2 ± 24.9 (130-160) mL, and the number of resected lymph nodes was 23 ± 8 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Patients who underwent hand-sewn esophagojejunostomy did not differ significantly from those who underwent conventional mechanical esophagojejunostomy ( Table 2).…”
Section: Surgery Detailsmentioning
confidence: 99%
“…In Table 1, literature that compares two anastomosis methods in a single institution is shown. [51][52][53][54][55][56] Five of the studies reported that morbidity such as anastomotic leakage and stricture were not significantly different in CS and LS methods; however, one report showed that the LS method has fewer complications.…”
Section: Reconstructionsmentioning
confidence: 99%
“…We reviewed anastomotic complications, especially those reported on leakage and stricture, in 43 extracted studies of LTG. 33,46,48,[52][53][54][55][56] We compared the surgical results of various anastomotic procedures for EJS using the CS, with attention to the insertion procedure of the anvil and the insertion site of the anastomotic device.…”
Section: Circular Staplermentioning
confidence: 99%